Decreased Norton's functional score is an independent long-term prognostic marker in hospital survivors of acute myocardial infarction. Soroka Acute Myocardial Infarction II (SAMI-II) project. (1st February 2017) - Silber, Hagar; Shiyovich, Arthur; Gilutz, Harel; Ziedenberg, Hanna; Abu Tailakh, Muhammad; Plakht, Ygal
Abstract: Background: Patient function is a risk factor of mortality following acute myocardial infarction (AMI). Norton scale (NS) was originally developed to estimate the risk for pressure ulcers. It contains 5 domains: mental condition, physical condition, mobility, activity in daily living and incontinence. Objective: To evaluate NS as long-term prognostic marker following AMI. Methods: A retrospective study based on computerized medical records of AMI patient hospitalized in a tertiary medical center in 2004–2012. NS scores and patients' characteristics were collected from computerized databases. The primary outcome was all-cause long-term (up-to 10-years) mortality. Results: Overall 6964 patients were included; mean age 67.3 ± 14.1 years, 68.1% males. Mean NS score was 17.8 ± 3; of which 21.1% had low-NS (≤ 16). Patients with low-NS had increased prevalence of hypertension, diabetes and renal disease, 3-vessel coronary artery disease, more often Non ST-Elevation Myocardial Infarction (NSTEMI) and in-hospital complications. Throughout the follow-up period cumulative mortality rate in patients with low- and high-NS groups were 97.3% and 43% respectively (AdjHR 1.66; 95% CI: 1.521–1.826; p < 0.001). Furthermore, a reduction in one point in the NS score inversely associated with increased risk for mortality (AdjHR 1.10; 95% CI: 1.12–1.22; p < 0.001). Conclusions: NS is an independent long-term prognostic marker for all-cause mortality in hospital survivors with a gradual "dose–response" effect. This data emphasizes the importance prognostic implication of the general functional status on the prognosis of AMI patients.